2013
DOI: 10.1111/j.1464-410x.2012.11673.x
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐assisted reconstructive surgery of the distal ureter: single institution experience in 16 patients

Abstract: What's known on the subject? and What does the study add? Open reconstructive surgery of the lower ureteric segment in adults often requires large incisions, as the basic prerequisite for such complex procedures is wide exposure. Published experience on minimally invasive techniques in this challenging surgical field, e.g. conventional laparoscopy or robot‐assisted laparoscopy, still remains limited. We report our experience from one of the largest single institution series on robot‐assisted reconstructive su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(25 citation statements)
references
References 31 publications
(58 reference statements)
0
24
0
1
Order By: Relevance
“…No complications were noted, all were asymptomatic, and none of the patients had radiologic evidence of disease at a mean follow-up of 15 months. Most recently, in 2013, Musch et al 11 reported on their experience with distal ureteral surgery in 16 patients for both malignant (n = 5) and benign (n = 11) conditions. Although operative times and length of stay were greater, these differences may be due to differences in technique (refluxing versus nonrefluxing) and healthcare systems (United States versus Europe).…”
Section: Discussionmentioning
confidence: 98%
“…No complications were noted, all were asymptomatic, and none of the patients had radiologic evidence of disease at a mean follow-up of 15 months. Most recently, in 2013, Musch et al 11 reported on their experience with distal ureteral surgery in 16 patients for both malignant (n = 5) and benign (n = 11) conditions. Although operative times and length of stay were greater, these differences may be due to differences in technique (refluxing versus nonrefluxing) and healthcare systems (United States versus Europe).…”
Section: Discussionmentioning
confidence: 98%
“…Recently, case series on robotic-assisted ureteral reimplantation including psoas hitch and Boari flap report outstanding functional outcomes of 94-100 % [55][56][57][58][59][60]. One study compared robotic and open ureteral implantation in 20 matched patients and reported EBL and hospital stay were significantly reduced in the robotic group, and although operative time was higher, this variable was not statistically significant [57].…”
Section: Functional Outcomes Ureteral Reconstructionmentioning
confidence: 96%
“…Over the last decade, the da Vinci robot has helped to bridge this gap 11,12 , and now allows urologists to perform efficient reconstructions of the upper urinary tract, such as pyeloplasty, ureterocystoneostomy or ureteral anastomosis 13,14 . To date however, laparoscopic reconstruction of the kidney graft urinary tract has not been addressed with the same enthusiasm.…”
Section: Introductionmentioning
confidence: 99%